The immorality of the Pyrrhonists - Correa Motta, Alfonso (Estudios de Filosofía, 2019)
In this paper I revisit Aristocles’ formulation of the objection of immorality addressed to the Pyrrhonists (apud Eusebio Praep. Ev. 14.18.18-19), as well as a possible skeptical answer transmitted by the same source (14.18.20). Concerning the objection, I will try to show that it is an ethical and not a practical charge, which should not therefore be confused with the objection of apraxia. Concerning the answer, I will argue that it is necessarily a de ationary solution, which leaves part of the accusation intact, simply because the Pyrrhonist cannot and should not admit the terms in which it has been raised.